Causal relationship between gut microbiota and myasthenia gravis: a two-sample Mendelian randomization study - Mi, Chuanhao; Hou, Ajiao; Wang, Ziyue; Qi, Xianghua; Teng, Jing (Frontiers in Neurology, 2024)
Background: Previous observational studies have provided cumulative data linking gut microbiota to myasthenia gravis (MG). However, the causal link between the two remains unexplored. Hence, the current study was performed to explore the causal link between them.Methods: Mendelian randomization (MR) analysis was conducted using the summary statistics of 211 gut microbiota taxa and the largest genome-wide association studies (GWAS) for MG currently available. The inverse variance-weighted (IVW), MR-Egger, weighted median, and weighted mode methods were employed to ascertain the causal influence. Sensitivity studies utilizing several methodologies were then used to assess the robustness of the findings. Lastly, to evaluate reverse causality, a reverse MR analysis was performed.Results: Seven suggestive causal associations between the gastrointestinal microbiota and MG were identified based on the outcomes of the MR analysis. Specifically, phylum Actinobacteria (OR: 0.602, 95% CI: 0.405-0.896, P = 0.012), class Gammaproteobacteria (OR: 0.587, 95% CI: 0.357-0.968, P = 0.037), and families Defluviitaleaceae (OR: 0.695, 95% CI: 0.485-0.996, P = 0.047), Family XIII (OR: 0.614, 95% CI: 0.412-0.916, P = 0.017), and Peptococcaceae (OR: 0.698, 95% CI: 0.505-0.964, P = 0.029) had suggestive protective effects on MG, while order Mollicutes RF9 (OR: 1.424, 95% CI: 1.015-1.998, P = 0.041) and genus Faecalibacterium (OR: 1.763, 95% CI: 1.220-2.547, P = 0.003) were suggestive risk factors for MG. The outcomes indicate that neither heterogeneity nor horizontal pleiotropy had any discernible impact. Nevertheless, this reverse analysis did not reveal any apparent effect of MG on the gut microbiota composition.The MR investigation has substantiated the suggestive causal connection between gut microbiota and MG, which may provide helpful insights for innovative therapeutic and preventative approaches for MG. Further randomized